PSIKATER DALAM SISTEM PERADILAN PIDANA - Ikhsan Alfarisi (AL WASATH Jurnal Ilmu Hukum, 2020)
Criminal law provides the requirement that said someone committing a crime must fulfill the element of action that is legally violated by law or has a normative nature against the law, in addition it is seen the causality of the criminal act with an element of error from within the perpetrator, meaning one's ability to be responsible. Here in lies the urgency of the existence of a psychiatrist in the criminal justice system in determining the degree of a person's ability to be responsible and the causality of actions with their mistakes. The purpose of this paper is to determine the role and position of psychiatrists in the criminal justice system. The research method in this paper uses literature research, with a juridical-normative approach meaning an approach based on legal rules as an abstract provision or in other words a method or procedure used to solve a problem by conducting research on secondary data . The results of the discussion showed the role of the psychiatrist as the legal agent of the law enforcement apparatus and in the criminal justice system as an expert in each stage of the examination in the criminal procedure law both in the investigation stage, additional examination in the prosecution and expert statement on the evidence at the trial.